Tough self-reporting elastomer with NIR induced shape memory effect. (December 2021) - Yang, Liulin; Ouyang, Pufan; Chen, Yuan; Xiang, Shishuai; Ruan, Yonghong; Weng, Wengui; He, Xumin; Xia, Haiping
Abstract : Multi-responsive polymers have attracted great attention in materials science. Herein, we report a tough self-reporting polyurethane elastomer with near infrared light induced shape memory. A radically exchangeable covalent 2, 2′-bis(2-phenylindan-l, 3-dione) bond is used as a dynamic covalent crosslink together with permanent crosslink and an organometallic complex carbolong 556 as a photothermal agent in the polyurethane network. The dynamic covalent 2, 2′-bis (2-phenylindan-l, 3-dione) bond, which is reversibly responsive to both thermal and mechanical stimuli, endows the elastomer with high toughness, mechanochromism, thermochromism, photothermochromism and shape memory behavior which can be triggered by direct heating or near infrared light irradiation mediated by the carbolong 556. Mechanochromism and thermochromism/photothermochromism are practically useful to self-reporting of mechanical failure and thermal condition, respectively. The near infrared light responsiveness facilitates a precisely spatial and temporal control of the shape memory behavior. This strategy opens up new opportunities to smart polymers. Graphical abstract: Image, graphical abstract